2017
DOI: 10.1186/s11671-016-1819-5
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene C60 Penetration into Leukemic Cells and Its Photoinduced Cytotoxic Effects

Abstract: Fullerene C60 as a representative of carbon nanocompounds is suggested to be promising agent for application in photodynamic therapy due to its unique physicochemical properties. The goal of this study was to estimate the accumulation of fullerene C60 in leukemic cells and to investigate its phototoxic effect on parental and resistant to cisplatin leukemic cells. Stable homogeneous water colloid solution of pristine C60 with average 50-nm diameter of nanoparticles was used in experiments. Fluorescent labeled C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 39 publications
0
31
0
3
Order By: Relevance
“…Lower TG-sensitive ER Ca 2+ pool content in the presence of photoexcited C 60 and cisplatin could [20].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Lower TG-sensitive ER Ca 2+ pool content in the presence of photoexcited C 60 and cisplatin could [20].…”
Section: Resultsmentioning
confidence: 96%
“…As it was previously shown by us with the use of fluorescent labeled C 60 and confocal microscopy, leukemic cells could effectively uptake fullerene C 60 from the medium [20]. Combined treatment of leukemic cells with photoexcited fullerene C 60 and 1 µg/ml cisplatin allowed us to enhance cytotoxic effect and to accelerate cell death of both sensitive and resistant to cisplatin cells as compared with each agent to be used alone [20,21], but the biochemical mechanisms of this effect need further elucidation. A substantial increase of [Ca 2+ ] cyt in leukemic cells which was detected 3 h after combined treatment with photoexcited C 60 and cisplatin [21] could be one of the determining factors in this effect.…”
Section: Abstract: Calcium Soce Leukemic Cells Cisplatin Dmentioning
confidence: 82%
“…79 reported the cytotoxic effect of C 60 in combination with visible light irradiation on leukemic L1210 cell lines, both sensitive and resistant to cisplatin. Their results suggest that C 60 -mediated photodynamic treatment is a good candidate for restoring drug-resistant leukemic cells induced to mitochondrial apoptosis.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…So, C 60 fullerenes behave as "free radical scavengers" and demonstrate antioxidant activity in micromolar concentrations, eliminating both H 2 O 2 and superoxide anions [9,10]. Due to its nearly spherical shape and nanosize, water-soluble C 60 fullerene is capable to penetrate plasma membrane of mammalian cells [11][12][13]. In vitro and in vivo studies of water-soluble pristine C 60 fullerenes had found that these compounds do not possess acute toxicity towards cells and tissues of human organism [14][15][16][17].…”
Section: Influence Of the Pristine C 60 Fullerene Aqueous Colloidal Smentioning
confidence: 99%